Addition Subtraction (Grand Haven, Mich School Zone Interactive, 2004)
Flash cards with atechno twist practice problems against the clock challenge another player to agame of fast facts or test for speed and accuracy
Ages 6+
System requirements for Windows: Pentium or faster ; Windows 95, 98 or higher ; 24 MB RAM ; 50 MB free disk space ; 640x480, 16-bit color video ; 16-bit sound card ; 4X CD-ROM drive. System requirements for Macintosh: PowerPC 601 or faster processor ; System 7.5.5 or higher ; 24 MB RAM ; 50 MB free disk space ; 640x480, 16-bit color video ; 4X CD-ROM drive
1 14
Keywords: games -- audiovisual; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs